Issues and recommendations in evaluating and managing the benefits of public sector IS/IT outsourcing - Lin, Chad; Pervan, Graham; McDermid, Donald (Emerald, 2007)
Purpose – The main purpose of this paper is threefold: to understand public-sector outsourcing in Australia; to examine the linkage between IS/IT outsourcing and the use of evaluation methodologies; and to identify issues that are critical in evaluating and managing IS/IT outsourcing contracts in public-sector organizations. Design/methodology/approach – A survey of the top 500 Australian organizations and two in-depth case studies of two Australian public-sector organizations were conducted. Findings – Several key issues for IS/IT outsourcing were identified – problems in evaluating outsourcing contracts, embedded contract mentality, ability to manage contracts, and staff transition management. Practical implications – Outsourcing organizations need to implement changes carefully and assess their in-house capabilities. They also need to fully understand and apply the IS/IT investment evaluation and benefits realization processes. In order to reach the magnitude of improvements ascribed to IS/IT outsourcing organizations need to undertake proper risk assessment and effectively manage outsourcing relationships. These all have to be done before and during the vendor/technology selection assessment and contract negotiation process. Originality/value – IS/IT outsourcing in the public sector is particularly under-studied. This study identifies several key issues for organizations undertaking IS/IT outsourcing. Recommendations are provided to assist outsourcing organizations in dealing with these issues.